A atividade orientadora de ensino como mediação no desenvolvimento de um jogo computacional - Prates, Uaiana e Silva (2011)
This study aims to examine to what extent the teaching oriented activities can contribute to the development of an educational computer game with the participation of students in the sixth year of Elementary Education. The teaching oriented activities were developed at first on paper in order to take into account oral and written elaborations of the students while the game was being "gestated". This strategy is based on current methodologies adopted in Computer Science, to build software or computer games that take into consideration the participation of users in the development process, such as "participatory design" or "user-centered design ". To utilize these methodologies we took into account some necessity encountered in the classroom by the actresses and actors of the research (teacher, student, programmer and researcher). The concern with educational computer games in the classroom is inspired on current pedagogical practices, where technology is increasingly being used and in some cases do not cause "real" changes in the traditional methodological approaches in the classroom. The construction of the data occurred in a public school in the inland of the state of São Paulo. The research question was defined as: to what extent the teaching oriented activities of geometric concepts can contribute to the development of an educational computer game with students in the sixth year of elementary school? The research was qualitative and the data analysis was constructed from the organization, reading and analysis of "teaching episodes." Such reviews are based on written and oral elaborations of students, identifying those that can assist on the development of educational computer game. We also intend to understand how such a process takes place, regarding the interaction among students, teacher, researcher and developer. As main findings we highlight the contribution of teaching oriented activities in the reveal of some unexpected situations throughout its development, which allow a special look as for some pedagogical aspects of the game. However, we emphasize a need to discuss some aspects that go beyond pedagogical issues, such as a necessary reconfiguration of the school aiming to promote dialogue with students of the twenty-first century. This reconfiguration is in the sense of conceiving a school that takes into consideration aspects of current society such as the networked information, its nonlinearity, as well as a school that prioritizes creativity and autonomy in educational processes.